Analysis of induced stress during construction and production stages of drawbells in block caving mines - Bustos, Nadia; Villaescusa, Ernesto; Garcia, Fernando (Institution of Mining and Metallurgy, 2024)
Drawbells are large constructions that allow the flow of the broken ore at the production level within the drawpoints. The results of drawbell construction are crucial for a successful mine plan extraction in a block caving mine. Analysis and integration of all the topics related to a drawbell can improve the performance of the surrounding area of drawbells, particularly the damage associated to induced stress during the different stages of a block caving operation. The improvement of operational aspects related to the drawbells would decrease the risk of failure, particularly in deep mines subject to large stresses, which are more likely to experience sudden violent or progressive failure. A large-scale numerical model was developed to analyse different mining sectors using sub-models. It was found that the geotechnical response is highly correlated to the stress field, which also controlled the resulting seismicity. In a scale of a drawbell, the drawpoint drift roof and the bridge pillar between the drawbell and the undercutting level were found the most critical zones in the design. When geological structures are present, they can be activated in the construction at an earlier stage and, therefore, could easily become critical in the resulting rock mass damage.